Development of a Human Literacy-Based Learning Model to Prepare Adaptive Pre-Service Teachers in the Faculty of Education - Yusnadi Yusnadi; Nani Barorah Nasution; Zuraidah Lubis; Kamtini Kamtini (International Journal of Educational Practice and Policy, 2026)
This study aimed to develop a human literacy-based learning model to prepare adaptive pre-service teachers in the Faculty of Education. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through questionnaires, observations, interviews, and documentation. The instruments included questionnaires, observation sheets, interview guides, and documentation checklists. Data were analyzed using descriptive quantitative and qualitative techniques. The findings showed that the model achieved a mean score of 3.66 for content validity and 3.75 for construct validity, indicating that it was highly valid. The practicality test also demonstrated positive results, with mean scores of 4.33 from students and 4.30 from lecturers, both categorized as highly practical. Furthermore, the effectiveness test yielded a mean score of 2.90, indicating a moderate level of effectiveness in improving students' human literacy competencies. The results suggest that the developed human literacy-based learning model is valid, practical, and effective for fostering adaptive competencies among pre-service teachers. Therefore, the model can serve as an innovative pedagogical framework for preparing future educators to address the challenges of twenty-first-century education.